PENGAMBILALIHAN SAHAM PERUSAHAAN MENURUT UU ANTIMONOPOLI (PERBANDINGAN HUKUM INDONESIA DENGAN KOREA SELATAN) - Nadya Angelina; Anna Maria Tri Anggraini (Fakultas Hukum Universitas Trisakti, 2021)
Competition law regulates the obligation to report the acquisition of company shares with certain requirements. However, each country regulates the reporting requirements with a different system, as well as Indonesia and South Korea. The problem formulation is how the regulation of the submission of share takeover reports according to Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition and the Monopoly Regulation and Fair Trade Act in South Korea, as well as differences in the application of reporting delays in takeovers in Indonesia and South Korea. Normative juridical research method using secondary data, analyzed using qualitative methods with deductive inference. The results of research, discussion and conclusion that the submission of a share takeover report in Indonesia is regulated in Article 29 of the Antimonopoly Law jo. Article 5 of Government Regulation No. 57 of 2010 and South Korea in Article 12 of the MRFTA. Both countries use a post notification reporting system, but South Korea stipulates mandatory pre-notification with certain limitations. The sanction for late reporting in South Korea is relatively smaller, which is ₩100,000,000.00, while the late fine in Indonesia is calculated daily up to a maximum of Rp 25,000,000,000.